Genome characterization of Shewanella algae in Hainan Province, China - Wang, Licheng; Chen, Shaojin; Xing, Mei; Dong, Lingzhi; Zhu, Huaxiong; Lin, Yujin; Li, Jinyi; Sun, Tuo; Zhu, Xiong; Wang, Xiaoxia (Frontiers in Microbiology, 2024)
Shewanella algae is an emerging marine zoonotic pathogen. In this study, we first reported the Shewanella algae infections in patients and animals in Hainan Province, China. Currently, there is still relatively little known about the whole-genome characteristics of Shewanella algae in most tropical regions, including in southern China. Here, we sequenced the 62 Shewanella algae strains isolated from Hainan Province and combined with the whole genomes sequences of 144 Shewanella algae genomes from public databases to analyze genomic features. Phylogenetic analysis revealed that Shewanella algae is widely distributed in the marine environments of both temperate and tropical countries, exhibiting close phylogenetic relationships with genomes isolated from patients, animals, and plants. Thereby confirming that exposure to marine environments is a risk factor for Shewanella algae infections. Average nucleotide identity analysis indicated that the clonally identical genomes could be isolated from patients with different sample types at different times. Pan-genome analysis identified a total of 21,909 genes, including 1,563 core genes, 8,292 strain-specific genes, and 12,054 accessory genes. Multiple putative virulence-associated genes were identified, encompassing 14 categories and 16 subcategories, with 171 distinct virulence factors. Three different plasmid replicon types were detected in 33 genomes. 11 classes of antibiotic resistance genes and 352 integrons were identified. Antimicrobial susceptibility testing revealed a high resistance rate to imipenem and colistin among the strains studied, with 5 strains exhibiting multidrug resistance. However, they were all sensitive to amikacin, minocycline, and tigecycline. Our findings clarify the genomic characteristics and population structure of Shewanella algae in Hainan Province. The results offer insights into the genetic basis of pathogenicity in Shewanella algae and enhance our understanding of its global phylogeography.